The Increased Ischemic Risk During the Early Period After Clopidogrel Noncompliance in Patients with Acute Coronary Syndrome: A Meta-Analysis - Yushan Li MD; Ruting Zhao MD; Peng Yu MD; Yan Xu MD; Quanyu Zhang MD; Yaling Han PhD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Although dual antiplatelet therapy for secondary prevention in acute coronary syndrome (ACS) is highly recommended by current guidelines, P2Y 12 inhibitor non-adherence often occurs and devastates prognosis. To evaluate whether the ischemic risk during the early period of clopidogrel noncompliance was increased among ACS patients, a comprehensive search of PubMed, Embase, and Web of Science was conducted to identify studies reporting early ischemic risk after clopidogrel noncompliance in ACS patients. The primary endpoint was a composite of death or myocardial infarction (MI). Effect sizes were synthesized in patients with or without revascularization. A total of 7 observational studies focusing on clopidogrel noncompliance were included in this meta-analysis, whereas no studies involving ticagrelor or prasugrel were retrieved. A significantly increased risk of death or MI 0 to 90 days after clopidogrel noncompliance was found compared with that during 90 to 180 or 90 to 360 days regardless of revascularization (incidence rate ratio [IRR]: 2.01, 95% confidence interval (CI): 1.62-2.49, P  < .001, I 2  = 9%) or not (IRR: 1.61, 95% CI: 1.05-2.48, P  < .001, I 2  = 74%). Patients undergoing percutaneous coronary intervention had a higher risk of death or MI 0 to 90 days after clopidogrel noncompliance compared with 90–180 or 90–360 days irrespective of drug-eluting stent or bare metal stent implantation ( P  < .05 for both). The early ischemic risk after clopidogrel noncompliance is significantly higher than the late risk in ACS patients. Antiplatelet noncompliance remains a serious concern.